Umbilical Cord as Prospective Source for Mesenchymal Stem Cell-Based Therapy - Irina Arutyunyan; Andrey Elchaninov; Andrey Makarov; Timur Fatkhudinov (Stem Cells International)
The paper presents current evidence on the properties of human umbilical cord-derived mesenchymal stem cells, including origin, proliferative potential, plasticity, stability of karyotype and phenotype, transcriptome, secretome, and immunomodulatory activity. A review of preclinical studies and clinical trials using this cell type is performed. Prospects for the use of mesenchymal stem cells, derived from the umbilical cord, in cell transplantation are associated with the need for specialized biobanking and transplant standardization criteria.